Carotid artery stents on CT angiography: in vitro comparison of different stent designs and sizes using 16-, 64- and 320-row CT scanners - Lettau, Michael; Kotter, Elmar; Bendszus, Martin; Hähnel, Stefan (Journal of neuroradiology, 2014)
Background and purpose - CT angiography (CTA) is an increasingly used method for evaluation of stented vessel segments. Our aim was to compare the appearance of different carotid artery stents in vitro on CTA using different CT scanners. Of particular interest was the measurement of artificial lumen narrowing (ALN) caused by the stent material within the stented vessel segment to determine whether CTA can be used to detect in-stent restenosis. - Material and methods - CTA appearances of 16 carotid artery stents of different designs and sizes (4.0 to 11.0 mm) were investigated in vitro. CTA was performed using 16-, 64- and 320-row CT scanners. For each stent, artificial lumen narrowing (ALN) was calculated. - Results - ALN ranged from 18.77% to 59.86%. ALN in different stents differed significantly. In most stents, ALN decreased with increasing stent diameter. In all but one stents, ALN using sharp image kernels was significantly lower than ALN using medium image kernels. Considering all stents, ALN did not significantly differ using different CT scanners or imaging protocols. - Conclusion - CTA evaluation of vessel patency after stent placement is possible, but is considerably impaired by ALN. Investigators should be informed about the method of choice for every stent and stent manufacturers should be aware of potential artifacts caused by their stents during noninvasive diagnostic methods such as CTA.